STRUKTUR DRAMATIK DAN ESTETIK FILM ANIMASI THE LITTLE KRISHNA - Harsakya, Cahya Surya (Capture : Jurnal Seni Media Rekam, 2016)
The focus of this research is dramatic structure and animation film aesthetic,The LittleKrishna. The study of this animation uses estetic interpretation analysis, while the type ofresearch is descriptive qualitative with fourth processes in collecting the data, namely datacollection, reduction, data analysis, and conclusion.The result shows that applying dramaticstructure (exposition, inciting-action, conflication, crisis, climax, resolution, and conclusion) inthe The Little Krishna describes the story well,whereas colour and genre as a point of interest inthis film.In addition,unity appears in the first segment telling not only about Krishna who lives inVrindavan village but also in the rural area itself. On the other hand, complexity seems in thirdsegment with multiple conflicts where Krisna was against both King Kamsa and God Indra.Besides, intensity appears in the last segment tells about Krishna who was serious in Vrindavanvillage to prevent the Kaliya snake attacks.Keywods : Animation,The Little Krishna,dramatic structure,dan aesthetic